Disease Incidence of Melon Leaf Curl in East Java and Special Province of Yogyakarta - Ignatius Julijantono; Susamto Somowiyarjo; Y. Andi Trisyono; Budi Setiadi Daryono (Universitas Gadjah Mada, 2010)
Geminivirus infection has caused severe losses on various economically important crops. The disease incidence on melon has been observed since 2004, and widespread at melon production centers in East Java and Special Province of Yogyakarta. In East Java and Special Province of Yogyakarta, the Disease Incidence of leaf curl on melon reached 100% and 14.3 % respectively in 2008. Detection of the causal agent using primers of CPA5 and CPA2 resulted viral specific DNA fragment of 770 bp.